Dynamics of Onset and Progression in Amyotrophic Lateral Sclerosis - Michael Swash; Mamede de Carvalho (Brain Sciences)
This review focuses on the complexities of amyotrophic lateral sclerosis (ALS) onset, highlighting the insidious nature of the disease and the challenges in defining its precise origin and early pathogenic mechanisms. The clinical presentation of ALS is characterised by progressive muscle weakness and wasting, often with widespread fasciculations, reflecting lower motor neuron hyperexcitability. The disease’s pathogenesis involves a prolonged preclinical phase of neuronal proteinopathy, particularly TDP-43 accumulation, which eventually leads to motor neuron death and overt ALS. This review discusses the difficulties in detecting this transition and the implications for early therapeutic intervention. It also addresses the involvement of both the upper and lower motor neuron systems, as well as the importance of following presymptomatic patients with genetic mutations. The significance of understanding the distinct processes of TDP-43 deposition and subsequent neuronal degeneration in developing effective treatments is emphasised.